Hubungan Gaya Hidup dengan Mean Arterial Pressure (MAP) Lansia Hipertensi Berbasis Transcultural Nursing di Puskesmas Rawalele - Regina Tianavissa; Eva Riantika Ratna Palupi; Dwi Diana Putri (Lembaga Pengembangan Kinerja Dosen, 2025)
An unhealthy lifestyle can increase the risk of blood vessel damage, heart disease, and hypertension, as well as increase Mean Arterial Pressure (MAP). Objective: This study aims to determine the relationship between lifestyle and Mean Arterial Pressure (MAP) in elderly hypertensive patients based on transcultural nursing at the Rawalele Community Health Center. Method: This study is a correlational analytic study using the Spearman Rank research design. The sampling method used in this study was purposive sampling. The total sample size was 157 respondents. The research instruments used were a lifestyle questionnaire and a digital sphygmomanometer. The Spearman Rank test results obtained a p-value of 0.000. Results: Based on the results of this study, it can be concluded that there is a relationship between lifestyle and Mean Arterial Pressure (MAP) in elderly hypertensive patients based on transcultural nursing at the Rawalele Community Health Center. With a p-value <0.05, it can be said that the variables are significantly correlated or related. This study is expected to provide a comparison for future researchers in educating and understanding lifestyle factors that can influence Mean Arterial Pressure (MAP) in elderly hypertensive patients.